Cardiorespiratory health and body composition of type 2 diabetics' patients: effect of a program of adapted physical activity - Teddy Bofosa; Eric Kam; Betty Miangindula; Donnell Muela; Constant Nkiama; François Njimbu (Turkish Journal of Kinesiology, 2018)
The Aim of this study is to verify the effects of adapted physical activity on the cardiorespiratory health and body composition of obese diabetic patients.  Thirty-two type 2 diabetes (T2D) patients (11 men, 21 women), aged 39-70 years, were randomly divided into two groups   according to body mass index, group 1: 20 overweight subjects (BMI <30) and group 2:  12 obese subjects (BMI> 30) undergoing a program Adapted physical activity of moderate intensity to severe during 3 months at the rate of 3 sessions of one hour per week. The paired student's t-test was used to evaluate the effect of the intervention program on the 6-minute walk test, arterial blood pressure, heart rate, weight, waist circumference, total fat, and visceral and lean mass. After 3 months of the practice of adapted physical activities, we observed significant changes in their resting heart rate of -6.06 bpm (p<0.05), systolic blood pressure of -7.8 mmHg (p<0.05), fasting blood glucose of -86.68mg/dl (p<0.05), maximum oxygen consumption of +6.13ml / kg / min (p<0.05), total fat of -5.89% (p<0.05), weight of -8.27kg (p<0.05), body mass index of -5.17 kg/m2 (p<0.05) and waist circumference of -5.66 cm (p<0.05) and their muscular percentage increased significantly by + 9.17%. Regular physical activity allows type 2 diabetics patients to improve their cardiorespiratory fitness and change their body composition.